Sequence analysis of earthworm hemolysins. Issue 2 (2004) - König König, Simone Simone; Wagner Wagner, Frank Frank; Kauschke Kauschke, Ellen Ellen; Eue Eue, Ines Ines
Abstract : Annelids are capable of defending themselves from pathogens and of recognizing degenerated self tissue. These reactions require specialized immune mechanisms that are effected by proteins and cellular reactions. Hemolytic proteins are the most striking humoral defense molecules in the earthworm Eisenia fetida . Beside their hemolytic activity these proteins possess agglutinating, antibacterial, cytotoxic, and clotting properties. Hemolytic proteins both from coelomocytes (CL39, 41 ) and coelomic fluid (H1−3 ) of wildtype E. fetida were isolated and assigned to fetidin and lysenin using mass spectrometry and bioinformatic tools. Glycosylation was found for H1 . In silico analyses of the hemolysins revealed two hemolysin isoforms and consensus sites for N-glycosylation and peroxidases proximal heme-binding ligand.